2022
DOI: 10.1093/jamiaopen/ooac033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of algorithms for identifying people with HIV from electronic medical records in a large, multi-site database

Abstract: Objective As electronic medical record (EMR) data are increasingly used in HIV clinical and epidemiologic research, accurately identifying people with HIV (PWH) from EMR data is paramount. We sought to evaluate EMR data types and compare EMR algorithms for identifying PWH in a multicenter EMR database. Materials and Methods We collected EMR data from 7 healthcare systems in the Chicago Area Patient-Centered Outcomes Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, ICD-9/10 codes provide a ubiquitous way for researchers to build predictive models using easily accessible data even if they lack the resources to carry out a review of medical records for every patient. Previous studies have shown that using ICD-9/10 codes can be effective at scaling up the rapid identification of people living with HIV [ 14 , 34 ]. Future studies should include social history variables and unstructured fields or free-text notes to see if they improve overall model performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ICD-9/10 codes provide a ubiquitous way for researchers to build predictive models using easily accessible data even if they lack the resources to carry out a review of medical records for every patient. Previous studies have shown that using ICD-9/10 codes can be effective at scaling up the rapid identification of people living with HIV [ 14 , 34 ]. Future studies should include social history variables and unstructured fields or free-text notes to see if they improve overall model performance.…”
Section: Discussionmentioning
confidence: 99%
“…Data contained sociodemographic information, encounter information, diagnosis codes, laboratory data, and antiretroviral therapy (ART) medication or prescription drug orders. We used the following criteria to determine if an individual was HIV-positive: (1) a positive HIV laboratory test (confirmatory HIV antibody, p24 antigen, or HIV viral load > 20 copies/mL), (2) an HIV viral load test performed (regardless of results) and prescription for ART, excluding pre-exposure prophylaxis prescriptions, (3) an HIV diagnosis code (International Classification of Diseases [ICD] version 9 [ICD-9] codes 42, 079.53, 795.71, and V08; ICD version 10 [ICD-10] codes B20, R75, and Z21) and a prescription for ART, excluding pre-exposure prophylaxis, or (4) an HIV diagnosis code and 2 HIV viral load tests performed [ 14 ]. Individuals were only included in the study if they met one (or more) of the above criteria and had at least two HIV care encounters.…”
Section: Methodsmentioning
confidence: 99%